Modelo animal de autismo induzido pela administração neonatal de lipopolissacarídeo de Escherichia coli: estudo de alterações comportamentais e neuroquímicas em animais infantes - Cristino, Larissa Maria Frota (2024)
The Autism Spectrum Disorder (ASD) is a neurodevelopment disorder in which an individual has limited communication and social interaction skills and has qualitative socio- communicative development compromised, as well as repetitive and restrictive behavior and interests. It is a complex behavioral syndrome that occurs mainly in male individuals, with multiple etiologies, and that combines genetic and environmental factors. Infections and stress have been associated with the occurrence of neuropsychiatric conditions, mainly at start of life, leading to alterations induced by inflammatory and/or neurotrophic mechanisms. Findings by our research team show that the exposure of newborn rats to Escherichia coli Lipopolysaccharides (LPS) can induce autism-like alterations dependent on sex in teenage or adult animals. In this context, we conducted experiences in Swiss mice, both male and female neonatally challenged (PN 5 e 7) with Escherichia coli LPS, aiming to understand the behavioral and neurobiological alterations in infant animals, as well as the influence of gender. Social interaction behavioral tests, both open field and Y maze tests were carried out on PN 25, equivalent to a 4-year-old human being. After behavioral assessments, the MPO activity, BDNF levels and expression of NF-kB, parvalbumin, IBA1 and synaptophysin were performed in the hippocampus and the pre-frontal cortex. Male mice exposed to LPS presented anxiety-like behavior, work memory deficit and repetitive behavior, whereas female individuals only presented reduced social interaction capabilities and work memory deficit. Female individuals treated with LPS presented in the hippocampus increased levels of IBA1 (HC), reduced parvalbumin (HC), and MPO activity, while in the PFC occurred BDNF alterations and decrease of the MPO activity. However, alterations observed in the same markers levels were not significant for male individuals. In summary, those were the main behavioral and neurochemical differences observed between male and female individuals exposed to LPS in this research. Our results show a differential vulnerability according to gender for various behavioral endophenotypes associated to ASD: males with cognitive alterations and stereotypy, and females with pro-social deficits.